Samorząd w nauczaniu społecznym Kościoła - Wójcik, Stanisław (Przegląd Politologiczny, 2018)
This paper contributes to the deliberations of a doctrinal and comparative nature. It indicates one of the sources providing for the dynamics of the evolution of self-government, the need to promote a new philosophy of self-government, and particularly emphasizes the significance of social personalism. Presentation of this issue allows better comprehension of various aspects of the ideological situation of self-government authorities and local communities.